PENGEMBANGAN BAHAN AJAR MENGGUNAKAN HAYZINE FLIPBOOK BERBASIS PROBLEM BASED LEARNING (PBL) DI KELAS V SEKOLAH DASAR NEGERI 1 TUMBUH MULIA TAHUN PELAJARAN 2023/2024 - Aediya Yusrina Diya; Muhammad Husni; Yul Alfian Hadi; Muhammad Sururuddin (STKIP Subang, 2024)
This study aims to develop teaching materials using Hayzine Flipbook based on Problem Based Learning (PBL) and examine its effectiveness in improving student understanding. The research method used was Research and Development (R&D) with the ADDIE development model which included the stages of Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study were using media expert and material expert validation sheets, educator questionnaires and student response questionnaires. The validation results by media experts with a score of 55 in the range of 51 < X ≤ 63 so that it can be categorized as “good” and for material experts with a score of 60 in the range of 51 < X ≤ 63 so that it can also be categorized as “good”. The results of the educator response questionnaire with a score of 38 in the range of 34 < ???? ≤ 42 so that it can be categorized as “practical”, while the results of the overall student responses got a score of 59.7 with an average of 4.26 so that it is in the range of X> 42.0 with the category “very practical”. The field trials conducted showed that this teaching material is effective in improving students' understanding of concepts. Students also gave a positive response to the use of this teaching material because it is more interesting and interactive than conventional teaching materials. Thus, the development of teaching materials using PBL-based Hayzine Flipbook can be used as an alternative in learning to improve the quality of education.